Towards Accurate Photogrammetry Using Molded Markers - Iñigo Auzmendi Iriarte; Oier Saez de Egilaz; Pedro Gonzalez de Alaiza Martinez; Imanol Herrera (Sensors)
Traditional marker-based photogrammetry systems often require the attachment and removal of a sticker for each measured point, involving labor-intensive manual steps. This paper presents an innovative approach that utilizes raised, cross-shaped markers, referred to as ‘molded markers’, directly embedded into composite pieces. In this study, these markers, commonly employed in other industrial processes, serve as fiducial markers for accurate photogrammetry. A two-stage detection algorithm is developed to accurately identify their centers: initial approximate detection by a Faster R-CNN model, followed by accurate localization using a classical cross center detection algorithm. This study investigates the pertinence of using polarimetric images to guarantee the highest detection rate and accuracy even in adverse lighting conditions. Experimental results demonstrate the viability of using these markers in accurate photogrammetry systems, achieving a median accuracy of 0.170 (interquartile range (IQR) 0.069 to 0.368) mm/m while enhancing automation and system usability.